Ischemic Heart Disease - Gaze, David C. (IntechOpen, 2013)
Cardiovascular disease (CVD) is ranked as the leading cause of death world wide, responsible for 17.1 million deaths globally each year. Such numbers are often difficult to comprehend. A coronary even occurs every 25 seconds and CVD kills one person every 34 seconds. 35 people under 65 years of age die prematurely every day due to CVD. The incidence of CVD has declined in recent years due to a better understanding of the pathology, implementation of lipid lowering therapy, new drug regimens and advances in acute surgical intervention. The disease burden has a great financial impact on global healthcare systems and major economic consequences for world economies. This text reviews the epidemiology, development, risk factors, diagnosis and treatment of ischemic heart disease.